MANAJEMEN KEARSIPAN PADA FAKULTAS VOKASI PELAYARAN UNIVERSITAS HANG TUAH - Mursidi, Mursidi; Widhi Yanti, Dyah Agustin (Unitri Press, 2023)
The goals of this study were to 1) analyze records management planning in improving the quality of academic services at the Maritime Vocational Faculty of Hang Tuah University. 2)nanalyze constraints on the implementation of archival management in improving service quality at the Maritime Vocational Faculty of Hang Tuah University. This research used observation, interview, and documentation methods which were submittedto respondents to obtain written information related to archives management. The technique for selecting researchsubjects is through purposive sampling technique. Based on the results of the analysis and discussion that has been carried out in this study, it can be concluded that in the field of administrative services. It has been going well because it has carried out procedures for manging records correctly, and if archives services are needed it does not take long to provide archives servoces for employees who need them related to the obstacles faced in managing archivesto improve services at The Maritime Vocational Faculty of Hang Tuah University, namely the unavailabilityof a special room for archives to ensure security and to get care for old archives so that they are not absolote and better guarantee the quality of the archives.